A review of factors that influenced online trust in social commerce - Noor A.D.; Sulaiman R.; Bakar A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electronic commerce; Social networking (online); eBusiness; Electronic business; Electronic word of mouths; Influential factors; New business models; Online business; Online trust; Social commerces; Commerce